EVALUASI PENYELENGGARAAN MALL PELAYANAN PUBLIK KABUPATEN BOJONEGORO DALAM RANGKA MENUJU PELAYANAN PUBLIK PRIMA - Suci Yanuar (Jurusan Administrasi Publik, Fakultas Ilmu Administrasi, Universitas Brawijaya, 2022)
Public Service Mall Bojonegoro received complaints and criticism from the community and from the Bojonegoro DPRD that there were still many service facilities and procedures that were not in accordance with the specified service standards. This study aims to analyze the evaluation of the implementation MPP in Bojonegoro, analyze the impact of MPP on the community and government of Bojonegoro, determine factors that influence the implementation MPP Bojonegoro. The research method used is descriptive qualitative. Based on the research, the implementation of MPP Bojonegoro shows a good evaluation result, but there are still some shortcomings that can be seen through the input, process, output, and outcome indicators. The impact of holding MPP in Bojonegoro on the community and the Government has both positive and negative impacts. Factors inhibiting the implementation MPP in Bojonegoro include inadequate human resources, lack of public knowledge about the existence of MPP Bojonegoro, and poor communication.